2011
DOI: 10.2147/ijn.s25427
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticulate formulations of mithramycin analogs for enhanced cytotoxicity

Abstract: Mithramycin (MTM), a natural product of soil bacteria from the Streptomyces genus, displays potent anticancer activity but has been limited clinically by severe side effects and toxicities. Engineering of the MTM biosynthetic pathway has produced the 3-side-chain-modified analogs MTM SK (SK) and MTM SDK (SDK), which have exhibited increased anticancer activity and improved therapeutic index. However, these analogs still suffer from low bioavailability, short plasma retention time, and lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 41 publications
1
17
0
Order By: Relevance
“…32 Then, to have an increased RB loading efficiency, better biocompatibility and pH-sensitivity for the RB-MMSNs, the polymer was grafted onto the surface of mesoporous silica by amidation reaction. C-O-C and C=O peaks belonging to PEG-b-PAsp advented in the FTIR spectrum of MMSNs 33 proved a successful grafting of PEG-b-PAsp onto the mesoporous silica surface ( Figure 4A).…”
Section: Resultsmentioning
confidence: 99%
“…32 Then, to have an increased RB loading efficiency, better biocompatibility and pH-sensitivity for the RB-MMSNs, the polymer was grafted onto the surface of mesoporous silica by amidation reaction. C-O-C and C=O peaks belonging to PEG-b-PAsp advented in the FTIR spectrum of MMSNs 33 proved a successful grafting of PEG-b-PAsp onto the mesoporous silica surface ( Figure 4A).…”
Section: Resultsmentioning
confidence: 99%
“…MTM SA-Trp was synthesized by chemical modification of MTM SA, which was produced by a procedure reported previously [32]. MTM SA-Trp was synthesized by coupling L-tryptophan methyl ester to the C-3 side chain of MTM SA.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous research demonstrated that CNAs prepared from biocompatible poly(ethylene glycol)-poly(aspartate) [PEG-p(Asp)] block copolymers provided stability for nanoparticles, by entrapping them in the core of a charged cage produced by locally highly concentrated carboxylate groups that isolate the CNAs and stabilize them from interaction among themselves and environmental cations. CNAs provide the ability to incorporate hydrophobic and amphiphilic payloads without changing particle size (23,33). CNA-IONP flux increased with time across bEnd.3 cells at 37°C, resulting in flux of less than 5% in 6 h. Flux across MDCKII cells was less than 0.2%.…”
Section: Discussionmentioning
confidence: 99%